Career plans of mentally superior young adults and selected indicators of developmental provisions - Mijares, Frances Olivia Alzona (2011)
This dissertation presented and discussed career plans (CP) of mentally superior young adults (MSYA) and the developmental provisions (DP) they received from their womb to school-aged years; and, explored significant differences among career plans according to four variables. It also determined correlations between significance of the career plans importance and satisfaction, and between career plans and developmental provisions. There were 68 Filipino participants; 34 MSYA (22 females and 12 males) and their respective mothers (34). The MSYA were single, aged 20 to 29, and rated to be superior in terms of IQ. This qualitative and quantitative study used two researcher-made sets of questionnaires and rating scales for the MSYA and another for the mothers. Nonparametric statistical methods were used.
"October 2011."
Thesis (Ph.D. Education : Special Education)--University of the Philippines, Diliman.
Keywords: Gifted persons -- Vocational guidance -- Philippines; Young adults -- Vocational guidance -- Philippines; Career education -- Philippines; Vocational interests -- Philippines; Mother and child -- Philippines